The Adventures of Huckleberry Finn - Andreasen Dan; Mark Twain (New York Sterling Publishing Co., Inc., 2006)
a young boy fleeing his abusive father, and Jim, a man escaping slavery, on a picaresque journey down the Mississippi River.
Keywords: a young boy escaping from his abusive father, and Jim, a runaway slave, as they travel down the Mississippi River in pre-Civil War America; value empathy and individual humanity over society's "deformed" conscience, culminating in his decision to protect Jim at the risk of his own salvation